2019
DOI: 10.1002/jat.3807
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific endocrine‐disrupting effects of three halogenated chemicals in Japanese medaka

Abstract: Several halogenated chemicals are found in an array of products that can cause endocrine disruption. Human studies have shown that endocrine responses are sex specific, with females more likely to develop hypothyroidism and males more likely to have reproductive impairment. The objective of this study was to assess sex differences on thyroid and estrogenic effects after exposure of Japanese medaka (Oryzias latipes, SK2MC) to halogenated compounds. This strain is an excellent model for these studies as sex can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…Recently, Dang et al (2021) reviewed the influence of thyroid hormone-disrupting chemicals on fish, including Japanese medaka and zebrafish. They noted that studies have shown changes in the expression of thyroid-related genes, such as thyroid stimulating hormone subunit beta (tshβ), thyroid hormone receptor alpha (trα), and beta (trβ), after exposure to the following chemicals: 2,2 0 ,4,4 0tetrabromodiphenyl ether in zebrafish (Chan & Chan, 2012), TDCPP in Japanese medaka (Godfrey et al, 2019) and in zebrafish (Wang et al, 2013), and 2-ethylhexyl-4-methoxycinnamate (EHMC) in Japanese medaka (Lee et al, 2019) and in zebrafish (Chu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Dang et al (2021) reviewed the influence of thyroid hormone-disrupting chemicals on fish, including Japanese medaka and zebrafish. They noted that studies have shown changes in the expression of thyroid-related genes, such as thyroid stimulating hormone subunit beta (tshβ), thyroid hormone receptor alpha (trα), and beta (trβ), after exposure to the following chemicals: 2,2 0 ,4,4 0tetrabromodiphenyl ether in zebrafish (Chan & Chan, 2012), TDCPP in Japanese medaka (Godfrey et al, 2019) and in zebrafish (Wang et al, 2013), and 2-ethylhexyl-4-methoxycinnamate (EHMC) in Japanese medaka (Lee et al, 2019) and in zebrafish (Chu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although exposure to TDCPP and EHMC causes changes in the expression of thyroid-related genes in both Japanese medaka and zebrafish, the reports then specified that, after exposure to TDCPP, trα and tshβ are upregulated in Japanese medaka (Godfrey et al, 2019) and zebrafish (Wang et al, 2013), and after exposure to EHMC, trα and trβ are upregulated in Japanese medaka (Lee et al, 2019) but downregulated in zebrafish (Chu et al, 2021). These results indicate that our understanding of how thyroid hormonedisrupting chemicals change the expression of genes related to thyroid hormone in Japanese medaka and zebrafish remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations